Formulasi Dan Evaluasi Fisik Sediaan Mouthwash Ekstrak Etanol Kulit Buah Matoa (Pometia Pinnata) - Nur Ain Thomas; Mahdalena Sy. Pakaya; Yayah Rachmatiyah; Ariani H. Hutuba (State University of Gorontalo, 2022)
Matoa peels contained phenolic, saponin, tannin, flavonoid and terpenoid which functions as anti-bacterias to Streptococcus mutans that can cause dental caries and active ingridients for mouthwash preparations. Mouthwash is a solution to be used as a cleansing agent that can improve mouth hygiene, esthetics and breath freshness. This study aimed to identify the etanol extract of Matoa peels to be formulated mouthwash preprations and its physical evalutions. This study employed methods that includes peels extraction, extract phytochemical screening, mouthwash preparation productions and mouthwash preparations evluations consisting of organoleptic, pH and viscosity test. The testing was conducted in day 0, 7, 14, 21 and 28. The findings revealed formula 2 as the best formula with 10% of glycerin concentration.